Vaccine strategies in gliomas - Platten, Michael; Bunse, Lukas; Bunse, Theresa; Wick, Wolfgang (Current treatment options in neurology, 2018)
To discuss the current state of glioma vaccine development and highlight the challenges associated with clinical implementation of these approaches. Vaccination strategies against gliomas have matured considerably during the past years, although proof-of efficacy from controlled clinical trials is still lacking. Advances in antigen discovery, including the definition of neoepitopes including epidermal growth factor receptor variant III (EGFRvIII), isocitrate dehydrogenase (IDH)1R132H and Histone (H)3.3K27M, using multi-omic approaches and computational algorithms allow targeting single antigens, but also implementing truly personalized approaches. In addition, new concepts of vaccine manufacturing including RNA and DNA vaccines improve immunogenicity and applicability in personalized settings. As an increasing amount of clinical data defy the concept of the central nervous system (CNS) as a strictly immunoprivileged site, novel vaccine approaches enter the clinic including critical efforts to identify biomarkers of response and resistance and strategies to overcome the immunosuppressive glioma microenvironment.
Gesehen am 23.04.2020